Art, emotion and ethics - Gaut, Berys (Oxford university press, 2007)
Can a great work of art be considered evil? Art, Ethics, and Emotion delves into this question, contending that artworks are always aesthetically imperfect to the extent that they possess a moral flaw that is relevant to their aesthetic value.
Includes bibliographical references and index.
Keywords: Aesthetics; Art - Aspect moral; Art - Moral and ethical aspects